The association between thyroid-stimulating hormone and thyroid nodules, goiter and thyroid antibody positivity - Li, Shaohan; Guo, Wenxing; Meng, Qi; Zhu, Mei; Wei, Hongyan; Ji, Fengying; Tan, Long; Zhang, Wanqi (Frontiers in Endocrinology, 2023)
The relationship between normal thyroid-stimulating hormone (TSH) levels and thyroid disease in adults remains controversial. This study aimed to investigate the correlation between serum TSH levels, particularly those falling within the normal range, and thyroid diseases in Chinese adults, including thyroid nodules (TN), goiter (GR), and thyroid antibody positivity. This research was a cross-sectional study conducted in an adult population in Tianjin, China. Thyroid volume (Tvol) and TN were assessed using thyroid ultrasonography. Fasting venous blood and spot urine samples were collected to evaluate thyroid function and iodine status. A total of 2460 subjects participated in the survey. The prevalence of thyroid dysfunction was 9.76%, and abnormal TSH levels were found to potentially increase the risk of GR and thyroid antibody positivity in adults. A total of 2220 subjects with TSH within the normal reference range were included in the further study. In these patients, Tvol decreased as TSH levels increased, in both men and women (P < 0.0001). Low TSH levels (0.27–1.41 IU/mL) were identified as a risk factor for TN (odds ratio [OR], 1.46; 95% CI: 1.14-1.87) and GR (OR 5.90, 95% CI 2.27-15.3). Upon stratification by sex and age, the risk of TN was found to be higher in women and elderly individuals (≥60 years old), while the risk of GR was found to be higher in men and younger individuals (<60 years old). High TSH levels (2.55–4.2 IU/mL) were identified as a risk factor for thyroid antibody positivity (OR, 1.53; 95% CI: 1.11-2.10). Men and younger individuals with high TSH levels exhibited a higher risk of thyroid antibody positivity. In adults with normal TSH levels, low TSH levels were associated with an increased risk of TN and GR, whereas high TSH levels were associated with thyroid antibody positivity. The research also suggests that adults whose TSH levels at upper or lower limits of the normal range should be reviewed regularly.